Launch of Esporo - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
1993 sees the launch of a new bi-monthly bulletin Esporo, published in Portuguese for distribution in lusophone African countries, Angola, Mozambique, Cape Verde, Guinea Bissau and Sao Tome and Principe. Esporo also serves as a link with other...